3^90-4*9^44+2^208÷(2*4^103)-5*(9^22)^2=
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
4
Explicație pas cu pas:
3^90-2²×3^88+2^208: 2×2^206-5×3^88=3^88×(9-4-5)+2²=0+4=4
Răspuns de
5
3⁹⁰-4×9⁴⁴+2²⁰⁸÷(2×4¹⁰³)-5×(9²²)²=
3⁹⁰-4×9⁴⁴+2²⁰⁸÷(2×(2²)¹⁰³)-5×9⁴⁴=
3⁹⁰-4×9⁴⁴+2²⁰⁸÷(2×2²⁰⁶)-5×9⁴⁴=
3⁹⁰-4×9⁴⁴+2²⁰⁸÷2²⁰⁷-5×9⁴⁴=
3⁹⁰-4×9⁴⁴+2-5×9⁴⁴=
3⁹⁰+2+9⁴⁴(-4-5)=
3⁹⁰+2+(-9)×9⁴⁴=
3⁹⁰+2-9⁴⁵=
2+3⁹⁰-(3²)⁴⁵=
2+3⁹⁰-3⁹⁰=
=2
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă